PELAKSANAAN KOKURIKULER MENTAL ARITMATIKA SEMPOA DI SDN LANDASAN ULIN BARAT 1 BANJARBARU - Sessi Rewetty Rivilla (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2014)
This study aims to determine the implementation of mental arithmetic abacus kokurikuler and knowing the subject matter of mathematics is supported kokurikuler abacus mental arithmetic in class I, II, III, and IV SDN Platform 1 Banjarbaru West Ulin. The method used in this research is descriptive method of research suggests that planning kualitatif.Hasil kagiatan kokurikuler Abacus Mental Arithmetic in West Ulin SDN Platform 1 has not been fully realized in practice in the field, so that the activities kokurikuler Abacus Mental Arithmetic Kindergarten takes place only on the level and no yng more students eager to continue to the next level. In general it can be said that the activities kokurikuler mental arithmetic in West Ulin SDN Platform 1 does not receive the attention and good control of the various parties seriously, either from school, UMC, board of teachers, instructors abacus, and parents / guardians of each student.